EFEKTIVITAS DAN KONTRIBUSI PAJAK RESTORAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA KUPANG - Djawang, Jofret Umbu Soru Peku (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
Restaurant tax is a type of regional tax to increase Regional Original Income (PAD) collected by the Kupang City government. It is known that the Kupang City government's restaurant tax revenue experienced fluctuations from 201-202. The purpose of this research is to describe the effectiveness and contribution of restaurant taxes in increasing Original Regional Income (PAD) in Kupang City. The results of the research on the average effectiveness of restaurant tax revenue in Kupang City on the PAD of Kupang City obtained a percentage result of 107,36 and was included in the very effective criteria, while the average contribution of restaurant taxes to Kupang City's original regional income was still in the very low category with a percentage value 9,75%. Suggestions to the Kupang City government to intensify and commit to increasing PAD by increasing awareness of Kupang City restaurant or restaurant entrepreneurs regarding the importance of paying taxes and making policies or strategies to increase restaurant or restaurant businesses in Kupang City.